Cantor lírico: conceituação e caracterização da expressividade - Pacheco, Natália Fonseca (2009)
INTRODUCTION: one of the branches of the Phonology actuation is the refinement of the professional voice and the expressiveness is one of the focuses of this work. Researchers have primordially come to grips with the spoken voice and a few works study the singing expressiveness, otherwise. PURPOSE: analyze the conceptualization and characterization of the expressiveness according the lyric singer. METHOD: as the method, 40 over 21 year old lyric singers were interviewed, and having all of then 3 year or more professional career. The instrument used for the data collection was the half-open questionnaire, elaborated for the research. The interviews were recorded and afterwards transcribed. The data analysis was based upon the methodology of Minayo (2004). RESULTS: data were initially coded. Then, were re-grouped according to their sense nucleuses, called thematic axles. From the singers answers, seven thematic axles were extracted: emotion/ feeling, surrender/donation, communication with the public, knowledge/study, vocal technic and text. According to the results, the lyric singer concept of expressiveness is connected to the emotion, feeling and also to the surrender. CONCLUSION: as final considerations, according to professional lyric singers, the expressiveness reports to the psyche, once, by those singers, the emotion and feelings are pointed as the expressiveness conductors. It is also clear that expressiveness is a subjective concept